Production and Characterization of Extracellular Protease from Bacillus sp. 140-B Isolated from Pineapple Plantation in Lampung, Indonesia - Laili, Nur; Antonius, Sarjiya (KnE Life Sciences, 2017)
Bacillus sp. being industrially important organisms produces a wide variety of extracellular enzymes including protease. Bacillus sp. 140-B isolated from rhizosphere area of pineapple plantation in Lampung Province, Indonesia was tested for production of protease on skim milk agar medium. The aims of this study were to characterize and investigate some properties of protease activity from Bacillus sp. 140-B. Bacillus sp. 140-B showed protease activity qualitatively by clear zone diameter of 15.0 mm and the highest protease activity was 35.02 Unit · mg–1 protein at 14 h after incubation. Some properties of protease activities from Bacillus sp. 140-B including effects of temperature, pH and several metals were observed in this experiment. The protease activity from Bacillus sp. 140-B had optimum pH of 7,0 and the optimum temperature was 60 °C. Several metals which were evaluated on protease activity showed that Mn could increase protease activity, while other metals (Ca, Co, and Hg) showed decreasing protease activity of Bacillus sp. 140-B. Keywords: Bacillus sp. 140-B; enzyme activity; enzyme properties; protease